Weak IPR and imitation in the south and international exhaustion of patent rights in the north for innovated drugs: A policy game - Rajat Acharyya; María del Carmen García-Alonso (University of Kent, School of Economics, 2009)
We consider a policy game between a high-income country hosting a drug innovator and a low-income country hosting a drug imitator. The low-income country chooses whether to enforce an International Patent Regime (strict IPR) or not (weak IPR) and the high-income country chooses whether to allow parallel imports (PI) of on-patent drugs or market based discrimination (MBD). We show that, for a moderately high imitation cost, both (Strict IPR, Parallel Imports) and (Weak IPR, MBD) emerge as the Subgame Perfect Nash Equilibrium (SPNE) policy choices. For relatively smaller imitation costs, (Weak IPR, MBD) is the unique SPNE policy choice. The welfare properties reveal that although innovation may be higher at the (Strict IPR, PI), the market coverage and national welfare of the low-income country, and the total welfare are all lower. This opens up the efficiency issue of implementing TRIPS and at the same time allowing international exhaustion of patent rights.
Keywords: D4; L1; I1; 330; patent protection; TRIPS; innovation; imitation; parallel imports; pharmaceuticals; Patentrecht; Internationale Wirtschaftsbeziehungen; Pharmazeutische Forschung; Innovation; Imitationswettbewerb; Nash-Gleichgewicht; Spieltheorie